DESARROLLO DE PRODUCTOS DE ALTO VALOR AGREGADO COMO ESTRATEGIA EXPORTADORA PARA LAS PYMES DEL SECTOR AGROINDUSTRIAL DE BOYACÁ DESDE LA PERSPECTIVA DE GESTIÓN DE PROYECTOS (2016)
The competitiveness of SMEs and any business is the result of a well-structured management designed to generate added value and increased the value chain in all processes of the organization projects, therefore the purpose of this article is to identify, conceptualize and project the added value as a key strategy for increasing the competitiveness of small business of Boyacá wishing to enter international markets, stimulating the generation of knowledge and epistemological development of an immersive way toward organizational structure resulting in a more effective planning and strategies in developing advanced products with differentiating power and greater acceptance in international markets strategically introducing the competitiveness of small business to the export of goods and / or services.